A Pilot Study on Counselor Trainees’ Social Justice Identity Development and Effective Pedagogy in a Multicultural Counseling Course - Shelby Messerschmitt-Coen; Gayle Garcia; Colette T Dollarhide; Damon Drew (Teaching and Supervision in Counseling, 2022)
Abstract: This pilot study examined social justice identity development for first- and second-year clinical and school counseling master’s students enrolled in a one-semester multicultural and social justice counseling (MCSJC) course. Counselor educators can incorporate social justice pedagogy in their courses to better equip counselors-in-training with the knowledge and skills necessary to act (Odegard & Vereen, 2010), which can foster the development of their social justice identities (Miller et al., 2009). Students enrolled in the MCSJC course reported their social justice identity at the beginning and end of the semester to determine identity development over time. In addition, pedagogical strategies were evaluated for their impact on identity development. Significant increases in social justice identity domains were found, with group differences based on year and track in the program. This study identified pedagogical strategies, such as cultural immersion activities, small group discussion, and guest speakers, that fostered students’ social justice identity development. What is the public significance of this article? This study suggests that social justice identity can be developed during a semester long, masters-level multicultural and social justice counseling course. Counselor educators can consider effective and intentional ways to incorporate various pedagogical strategies in their curriculum to foster the growth of students’ social justice efficacy and engagement, and the present study offers empirically-based evidence of such effective pedagogy.
Keywords: social justice; pedagogy; counselor education